Penggunaan Probiotik Dan Magot Untuk Mereduksi Lalat di Peternakan Ayam Pedaging Muara Selayar Desa Pijot - Muhamad Ali; Made Sriasih; Anwar Rosyidi; I Wayan Wariata; Muh. Aidil Fitriyan Fadjar Suryadi; Nefi Andriana Fajri; Sulaiman Ngongu Depamede (Universitas Mataram, 2022)
Chicken manure waste is one of the main problems for large-scale broiler cultivation, especially in areas close to residential areas. The accumulation of manure that accumulates under the cage attracts the arrival and development of the flies in the cultivation site. The development of these flies will spread to the houses of residents who live around the cage. As a result, many farmers stop cultivating the broilers because of public complaints. To overcome this problem, the use of probiotics from acetic acid-producing bacteria can be used to reduce the development of flies because of the ability of the bacteria to reduce the pH of the media and create an uncomfortable environment for egg growth. Likewise, the development of maggot can be a competing medium that beats the flay. In community service activities regarding